2020
DOI: 10.22159/ijap.2020.v12s2.pp-20
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus Reuteri Effect’s on the Levels of Interleukin-4 in Periodontitis Patients After Scaling and Root Planing

Abstract: Objective: Periodontal disease is an inflammatory disease principally caused by a complex interaction between pathogenic bacteria and immuneresponses. Probiotics stimulate the immune system of the oral mucosa by increasing the production of anti-inflammatory cytokines. Interleukin-4 (IL-4) isthe anti-inflammatory cytokine that is most closely associated with the pathogenesis of periodontitis. This study assessed the effect of Lactobacillus reuteri(L. reuteri) containing probiotic lozenges toward clinical attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Then, the literature search on the influence of L. reuteri in the nonsurgical treatment of periodontal disease resulted in 9 articles considering current scientific evidence, which met the inclusion and exclusion criteria, and were integrated in this systematic review (k = 0.99) (Figure 1). They were codified to facilitate the description: S1 (Teughels et al, 2013) [21]; S2 (Tekce et al, 2015) [22]; S3 (Pelekos et al, 2019) [15]; S4 (Ikram et al, 2019) [23]; S5 (Sinulingga et al, 2020) [10]; S6 (Pelekos et al, 2020) [24]; S7 (Hadžić et al, 2021) [25]; S8 (El-Bagoory et al, 2021) [26]; and S9 (Sufaru et al, 2022) [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the literature search on the influence of L. reuteri in the nonsurgical treatment of periodontal disease resulted in 9 articles considering current scientific evidence, which met the inclusion and exclusion criteria, and were integrated in this systematic review (k = 0.99) (Figure 1). They were codified to facilitate the description: S1 (Teughels et al, 2013) [21]; S2 (Tekce et al, 2015) [22]; S3 (Pelekos et al, 2019) [15]; S4 (Ikram et al, 2019) [23]; S5 (Sinulingga et al, 2020) [10]; S6 (Pelekos et al, 2020) [24]; S7 (Hadžić et al, 2021) [25]; S8 (El-Bagoory et al, 2021) [26]; and S9 (Sufaru et al, 2022) [27].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, implementing the association (Amoxicillin with Metronidazole) creates more favorable clinical and microbiological effects than Metronidazole alone, despite presenting more adverse effects [ 8 ]. The greatest question is cases of microbial resistance [ 9 ], recolonization in the same sites, and possible adverse effects [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review and meta-analysis showed that periodontal clinical parameters (Pl, GI, CAL, BOP, and PPD) and subgingival microbial outcomes differed significantly following probiotic supplementation relative to control treatment. A large number of experiments have demonstrated that the adjuvant treatment of chronic periodontitis with probiotics is clinically beneficial (Mayanagi et al, 2010;Sinulingga et al, 2020). However, no standard probiotic regimen is given to patients, with variations in reported dose, administration route, carrier form, and duration.…”
Section: Discussionmentioning
confidence: 99%